The Effect of Wealth on Individual and Household Labor Supply: Evidence from Swedish Lotteries - Cesarini, David; Lindqvist, Erik; Notowidigdo, Matthew J.; Östling, Robert (American Economic Review, 2017)
We study the effect of wealth on labor supply using the randomized assignment of monetary prizes in a large sample of Swedish lottery players. Winning a lottery prize modestly reduces earnings, with the reduction being immediate, persistent, and quite similar by age, education, and sex. A calibrated dynamic model implies lifetime marginal propensities to earn out of unearned income from −0.17 at age 20 to −0.04 at age 60, and labor supply elasticities in the lower range of previously reported estimates. The earnings response is stronger for winners than their spouses, which is inconsistent with unitary household labor supply models. (JEL D14, J22, J31)